Arsiparis dalam era digital: analisis bibliografi tentang perkembangan arsiparis dalam database internasional menggunakan vosviewer - Jalinur, Jalinur (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research analyzes the trends in archival research from 1939 to the present. The study aims to determine: (1) the development of the number of international publications on archiving in the Scopus database from 1939 to 2023; (2) journals in international publications about archivists; (3) the productivity of the authors; (4) the number of publications based on institutional collaboration in international publications about archivists; (5) the development of international publications on archivist research by subject/field; (6) the mapping of the development of international publications on archivist research based on co-occurrence. Data collection methods involved searching the Scopus database with the keyword